Answers:
After simplifying the following expression, the coefficient of the m^2 term will be 13
The solution is 13m^2 + 6mn^2 - 5nm^2
====================================================
Step-by-step explanation:
Highlight all the terms that have m^2 in them and nothing else (so that means no variables of n or n^2)
You should highlight 3m^2, 16m^2 and -6m^2 as the three terms.
The coefficients 3, 16 and -6 combine to 3+16-6 = 13
Meaning that 3m^2+16m^2-6m^2 = 13m^2
----------------
There are no other like terms that pair up.
The 6mn^2 and -5nm^2 are different because the exponent 2 is over a different letter each time. Put another way: mn^2 is not the same as nm^2
So we cannot combine 6mn^2-5nm^2. We leave it as is.
Overall, the entire expression simplifies to 13m^2 + 6mn^2 - 5nm^2